2018
DOI: 10.1016/j.cell.2018.04.027
|View full text |Cite|
|
Sign up to set email alerts
|

The Gut Microbiota Mediates the Anti-Seizure Effects of the Ketogenic Diet

Abstract: The ketogenic diet (KD) is used to treat refractory epilepsy, but the mechanisms underlying its neuroprotective effects remain unclear. Here, we show that the gut microbiota is altered by the KD and required for protection against acute electrically induced seizures and spontaneous tonic-clonic seizures in two mouse models. Mice treated with antibiotics or reared germ free are resistant to KD-mediated seizure protection. Enrichment of, and gnotobiotic co-colonization with, KD-associated Akkermansia and Parabac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
618
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 724 publications
(642 citation statements)
references
References 55 publications
19
618
3
2
Order By: Relevance
“…Of the downregulated genera, Lachnospiraceae are the most prominent. These changes, like those we observed in ketone body profiles, are reminiscent to those induced by ketogenic diets, and are associated with the reduction of epileptic seizures (Olson et al, ).…”
Section: Discussionsupporting
confidence: 78%
“…Of the downregulated genera, Lachnospiraceae are the most prominent. These changes, like those we observed in ketone body profiles, are reminiscent to those induced by ketogenic diets, and are associated with the reduction of epileptic seizures (Olson et al, ).…”
Section: Discussionsupporting
confidence: 78%
“…This study, as admitted by the authors, is preliminary and lacks mechanistic insight. However, it complements a study that appeared almost concurrently showing that the effects of the ketogenic diet on seizures in mice were mediated by changes in the gut microbiome . It is interesting that the current study did not reveal any alteration in brain excitability (revealed by after‐discharge threshold) as a function of the transplantation of the “stress” microbiota.…”
supporting
confidence: 76%
“…The human commensal Bacteriodes is protective against behavioral deficits seen in the MIA model [124]. Finally, bacterial species that reduce gamma-glutamyl amino acids may be responsible for some of the benefits of the ketogenic diet, widely used in intractable epilepsy and, despite weaker evidence, recommended by some for treatment of autism [126]. While much remains to be determined about direct versus indirect effects of the microbiome on the brain, defining the underlying mechanisms represents an exciting area for further study with many potential therapeutic implications.…”
Section: The Gut-brain Axis In Modulation Of Immune Tonementioning
confidence: 99%